Políticas públicas de desenvolvimento territorial no Brasil (2003-2016): um estudo do território sudoeste paulista (SP) - Antunes Junior, Wolney Felippe (Universidade Federal de São Carlos, 2020)
Between 2003 and 2016, Brazil has experimented with a series of decentralized public policies, some of which have adopted the territorial approach. These include the "Fome Zero" Program, through the Food Security and Local Development Consortia (CONSAD); the National Program for Sustainable Development of Rural Territories (PRONAT); and the Citizenship Territories Program. The Sudoeste Paulista, due to its historicity and its low Human Development Index (HDI), was one of the territories elected by the Federal Government and has passed through the three programs mentioned above. Among advances and challenges, experiences with territorial policies still have a wide field to be debated. In this sense, the objective of this research was to study the public policies of territorial development implemented in Sudoeste Paulista and to analyze the acting capacities of its institutional arrangements. This study took place through the performance of CONSAD Sudoeste Paulista, which was the territorial collegiate in these three territorial policy programs. As methodology were used the semi-structured interviews and documentary analysis. Among the main results, it can be said that: the territorial collegiate did not cover all the diversity of the territory and alternated between periods when the centrality was in the demands of the public power and periods in which civil society was more active; projects and actions were mostly defined under top-down movements and the territory functioned as a locus of government investment; The challenge of promoting innovative, intersectoral and intermunicipal actions can be understood by the technical-administrative and politicalrelational capacities of institutional arrangements and the policy design stipulated by the policies. If, on the one hand, public policies for territorial development presented several contradictions and limitations, on the other hand, it must be recognized that this is a process of experimentation, in which learning and lessons have been accumulated along their trajectory.
Public policies of territorial development in Brazil (2003-2016): a study from the southwest paulist territory (SP)
Keywords: Arranjos institucionais; Governança; CONSAD; Colegiado territorial; Institutional arrangements; Governance; Territorial collegiate; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS